Incidence and Control of Selakarang Disease In Horses - Riza Zainuddin Ahmad; S Anis (Indonesian Center for Animal Research and Development, 2012)
Selakarang is a fungal disease attacking horses. Although the mortality rate is low, the morbidity is high leading to economic loss. The island of Sulawesi has about 151.000 horses and they are distributed in 5 provinces: North, Central, West, South, and South-East Sulawesi which potentially has endemic outbreaks caused by the Selakarang fungus, Histoplasma farciminosum. The disease might be endemic throughout Indonesia if the horse trading is not monitored. In Maros, South Sulawesi, the disease is found with symptoms in the form of nasal, cutan, and ocular symptoms. Ignorance of the appropriate authorities will increase the likelihood of spread of the disease. According to the Staatblad act produced in 1912 and the disease belonged to the zoonotic disease and when it is not well handled and properly managed, infection to human may occur. Prevention is better than treatment. In the future, we may propose to produce inactive vaccines and develop serological test to detect antigen and antibody in RIVS collaborating with other government agencies or private parties interested in this disease control. Key words: Horse, Selakarang Disease, Sulawesi